Os efeitos da internal stickiness no sucesso dos projetos: a percepção dos gestores - Araujo, Valdemilson de Assis Alves de (2019)
Many authors have devoted themselves to studying knowledge transfer, mainly as an important aspect for companies' competitive advantage, as well as for projects. Project managers and those involved in project teams are seen by theorists as factors that can influence both project success and the opposite. The concept of Internal Stickiness is a term used to illustrate something that is 'sticky' and difficult to transfer. The purpose of this study is to investigate the effects of Internal Stickiness on project success by designing the managers involved in the projects. Firstly, the theme was born from a bibliometric study of citation, cocitation and pairing. In citation and citation studies, it was possible to identify the intellectual structure of research on Internal Stickiness from the references in publications on this subject. However, in the pairing analysis it was possible to identify the existing research on Internal Stickiness, focusing on understanding and understanding what has been studied today. Second, a quantitative research was conducted to validate the Stickiness scale in the Brazilian context. A survey was applied online by Google Forms, through which it was possible to validate this scale with 150 project managers as valid respondents. Third, shortly after scale validation it was possible to investigate the effects of Internal Stickiness (independent variable) on project success (dependent variable). The research was quantitative with online survey through Google Forms, with the participation of 253 project managers. In the results, the proposed hypothesis was tested and confirmed. The results support the broad hypothesis that IS, when considering barriers to knowledge transfer, negatively influences project success.